Candidemia in Pediatric-Clinic: Frequency of Occurrence, Candida Species, Antifungal Susceptibilities, and Effects on Mortality (2020–2024) - Kamuran Şanlı; Esra Arslantaş; Ayşe Nur Ceylan; Beyza Öncel; Duygu Özkorucu; Ayşe Özkan Karagenç (Diagnostics, 2024)
Objective: Invasive candidiasis is defined as an important infection that increases the duration of patients’ hospital stay, costs, mortality and morbidity. In this study, we aimed to investigate the frequency of candidiasis in blood cultures of pediatric hematology patients, Candida species, antifungal susceptibilities, and their effects on mortality. Materials and Methods: Patients with Candida growth in their blood cultures at follow-up in the pediatric hematology clinic of our hospital between 2020 and 2024 were included in the study. Age, gender, primary diseases and risk levels, subtypes and antifungal susceptibilities of Candida grown in blood cultures, the presence of neutropenia in patients, the antifungals used for prophylaxis and treatment, the duration of infection, other bacteria grown additionally during the fungal infection period, the local infection source and the patients’ discharge status were obtained from medical records. These constituted the study data. Results: Blood cultures were requested for 594 patients from the Pediatric hematology Clinic, and Candida was grown in only 37 (6.7%) of them. A total of 43.2% of them were the Candida parapsilosis complex, 29.7% were Candida albicans and 8.1% were the Candida haemulonii complex. Antifungal susceptibilities were over 90% for anidulafungin, micafungin, caspofungin, posaconazole, itraconazole and amphotericin B, followed by 86.7% for fluconazole and 84.4% for voriconazole. The mean age of the patient group was 6.8 years, 50.5% of whom were female and 40.5% of whom were male. The Candida infections developed on the 12.1th day of the neutropenia process on average. The mean invasive Candida infection period was 7 days. A total of 18.9% had a second bacterial infection and 13.5% had a local infection. A total of 51.4% had a single antifungal, 18.9% had two antifungals and 2.1% had more than two antifungals. A total of 35.1% of the patients with invasive candidiasis died. The primary diagnosis of the disease, Patient risk level, and the female gender were important factors affetting mortality. Conclusions: In a pediatric hematology clinic, the non-albicans group in invasive candidiasis infections was notable, with the C. parapsilosis complex occurring most frequently. There was still a high sensitivity to echinocandin antifungals and a decreased sensitivity to triazoles. It was found that the factor of the clinical diagnosis, being in the high-risk group and being female had significant effects on the survival rate of patients with candidiasis infections.